2023
DOI: 10.7554/elife.86939
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic polyglutamine aggregation begins with a self-poisoning polymer crystal

Abstract: A long-standing goal of amyloid research has been to characterize the structural basis of the rate-determining nucleating event. However, the ephemeral nature of nucleation has made this goal unachievable with existing biochemistry, structural biology, and computational approaches. Here, we addressed that limitation for polyglutamine (polyQ), a polypeptide sequence that causes Huntington’s and other amyloid-associated neurodegenerative diseases when its length exceeds a characteristic threshold. To identify es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 212 publications
0
4
0
Order By: Relevance
“…We previously showed that discontinuous transitions result from large structural nucleation barriers that are characteristic of prion-like self-assembly. 43,46,53 We find this to be a surprisingly large number given the paucity of proteins with known prion-like behavior. For example, a systematic DAmFRET screen of the top 100 computationally predicted yeast prion-forming proteins found that only 14 exhibited discontinuous DAmFRET profiles.…”
Section: Nucleation Barriers Are Prevalent Among Dfdsmentioning
confidence: 96%
See 1 more Smart Citation
“…We previously showed that discontinuous transitions result from large structural nucleation barriers that are characteristic of prion-like self-assembly. 43,46,53 We find this to be a surprisingly large number given the paucity of proteins with known prion-like behavior. For example, a systematic DAmFRET screen of the top 100 computationally predicted yeast prion-forming proteins found that only 14 exhibited discontinuous DAmFRET profiles.…”
Section: Nucleation Barriers Are Prevalent Among Dfdsmentioning
confidence: 96%
“…We then analyzed the data as previously described. 53 Briefly, FCS files were gated using an automated R-script running in flowCore. Before gating, the forward scatter (FS00.A, FS00.W, FS00.H), side scatter (SS02.A), donor fluorescence (FL03.A), and autofluorescence (FL17.A) channels were transformed using a logicle transform in R. Single cells were gated using FS00.A vs SS02.A and FS00.H vs FS00.W.…”
Section: Damfret Data Analysismentioning
confidence: 99%
“…Computational modeling also suggests that the nucleation of smaller polyQ fragments promotes elongation and fibrillation by reducing the conformational entropy of interacting monomers in a concentration-dependent manner (Phan and Schmit 2022). Recently, Halfmann and colleagues confirmed the formation of a monomeric nucleus in vivo for the pathogenic polyQ 60 fragment and determined its structural features using an integrative modeling approach (Kandola et al 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…While higher-order oligomerization through N17 significantly increases the local concentration of polyQ tracts (‘proximity’ model), such a mechanism alone fails to explain the enhanced rate of polyQ aggregation as forcing a high local concentration of polyQ by fusing it to homo-oligomeric partners suppresses its fibrillar aggregation in vitro (Kokona et al 2014) and in vivo (Kandola et al 2023a). Two additional models were proposed to explain the conversion of Httex1 oligomers into aggregates via polyQ expansion (Kokona et al 2014): (i) ‘transformation’ model, i.e., the propagation of N17 helical secondary structure into the polyQ tract and, (ii) ‘domain cross-talk’ model, i.e., tertiary interdomain interactions between N17 and polyQ domains.…”
Section: Introductionmentioning
confidence: 99%